PEMENUHAN PERLINDUNGAN HAK ANAK SEBAGAI TERSANGKA TINDAK PIDANA PENCURIAN DI KOTA PALOPO - Darwis, Muh.; Ridwan (Datuk Sulaiman Law Review (DaLRev), 2024)
This article discusses protecting children's rights as suspects of theft crimes in Palopo City from the perspective of Islamic law. This research uses qualitative methods and primary and secondary data. The results show that the police play a role in tackling the protection of children's rights, such as interviewing victims, searching for evidence, and cooperating with community leaders and social workers. The police also persuaded the child's family to facilitate the investigation. Children have rights, including legal assistance in the investigation process, especially for parents or people who cannot afford it. Investigators must also inform suspects who are under investigation of their rights under KUHAP, and if they are not accompanied by a legal representative, irregularities such as detention without sufficient evidence may occur.